1989
DOI: 10.1104/pp.91.3.876
|View full text |Cite
|
Sign up to set email alerts
|

Culm Strength of Barley

Abstract: Grass culms are known to differ in breaking strength, but there is little physicochemical data to explain the response. The fourth intemode of four brittle and two nonbrittle barley (Hordeum vulgare L.) strains were used for physical and chemical studies of culm strength. Inner and outer culm diameters of brittle strains (3.6 ± 0.2 and 5.0 ± 0.1 millimeters) were not significantly different from those of nonbritte strains (3.9 ± 0.2 and 5.2 ± 0.2 millimeters). Maximum bending stress, at which the culm was brok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(63 citation statements)
references
References 9 publications
(8 reference statements)
1
61
1
Order By: Relevance
“…Chapin 1980;Lambers & Poorter 1992). The higher amount of cell wall material in leaves of species from nutrient-limited environments points to an increase in the strength (Bell 1981;Kokubu, Kuraishi & Sakurai 1990) and reduced digestibility (Bazzaz et al 1987;Kephart, Buxton & Hill 1990) of the leaves of species from environments where the nutrient supply is scarce. Both fast-and slow-growing grasses show a higher concentration of cell wall components under limiting nitrate supply.…”
Section: Ecological Implications '• • • • Mmentioning
confidence: 99%
“…Chapin 1980;Lambers & Poorter 1992). The higher amount of cell wall material in leaves of species from nutrient-limited environments points to an increase in the strength (Bell 1981;Kokubu, Kuraishi & Sakurai 1990) and reduced digestibility (Bazzaz et al 1987;Kephart, Buxton & Hill 1990) of the leaves of species from environments where the nutrient supply is scarce. Both fast-and slow-growing grasses show a higher concentration of cell wall components under limiting nitrate supply.…”
Section: Ecological Implications '• • • • Mmentioning
confidence: 99%
“…Our previous study (15) of brittle culms of three barley mutants generated by a mutagen and Kamairazu mutant whose genetic background was not known revealed that the mutants contain less cellulose in the cell wall than the normal strains. Comparison between normal and isogenic brittle strains is necessary for genetic and biochemical analyses.…”
mentioning
confidence: 99%
“…The chemical compositions and physical strength of the cell wall were also determined. (15). Sections (7 cm) of the fourth internode kept in methanol were rehydrated for 2 h in 300 mL of deionized water at room temperature.…”
mentioning
confidence: 99%
See 2 more Smart Citations